2009
DOI: 10.1089/clo.2009.0004
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of Human Somatic Cells Using Human and Animal Oocytes

Abstract: There is renewed interest in using animal oocytes to reprogram human somatic cells. Here we compare the reprogramming of human somatic nuclei using oocytes obtained from animal and human sources. Comparative analysis of gene expression in morula-stage embryos was carried out using single-embryo transcriptome amplification and global gene expression analyses. Genomic DNA fingerprinting and PCR analysis confirmed that the nuclear genome of the cloned embryos originated from the donor somatic cell. Although the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
4

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 28 publications
6
55
4
Order By: Relevance
“…Control SPNT cow and sheep embryos as expected developed to the blastocyst stage; however, none of the cow-sheep or sheep-cow iSPNT embryos developed beyond the 8-to 16-cell stage, again the stage at which EGA occurs in both species. Taken together, our results support the argument that development of inter-species nuclear transfer embryos is highly inefficient with developmental arrest occurring at the stage of EGA specific to recipient cytoplast species (Chung et al 2009, Lagutina et al 2010. These recent reports have clearly demonstrated that the donor nucleus in iSCNT is only partially remodeled by the heterologous cytoplasm, and iSCNT embryos need to overcome nuclear-cytoplasmic compatibility issues before any further embryonic development to the blastocyst or later stages can be expected (Chung et al 2009, Lagutina et al 2010.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Control SPNT cow and sheep embryos as expected developed to the blastocyst stage; however, none of the cow-sheep or sheep-cow iSPNT embryos developed beyond the 8-to 16-cell stage, again the stage at which EGA occurs in both species. Taken together, our results support the argument that development of inter-species nuclear transfer embryos is highly inefficient with developmental arrest occurring at the stage of EGA specific to recipient cytoplast species (Chung et al 2009, Lagutina et al 2010. These recent reports have clearly demonstrated that the donor nucleus in iSCNT is only partially remodeled by the heterologous cytoplasm, and iSCNT embryos need to overcome nuclear-cytoplasmic compatibility issues before any further embryonic development to the blastocyst or later stages can be expected (Chung et al 2009, Lagutina et al 2010.…”
Section: Discussionsupporting
confidence: 88%
“…However, all intra-species SCNT embryos produced under the same conditions used for iSCNT developed to blastocyst stage. Our results were not different from several other recent reports (Chung et al 2009, Lagutina et al 2010, who had also reported that iSCNT embryos failed to reactivate the embryonic genome and arrested at the stage of EGA specific to the recipient oocyte. Conversely, inter-genus (Oh et al 2006, Yin et al 2006, inter-family (Dominko et al 1999, Zhao et al 2007, inter-order (Yang et al 2003, Wen et al 2005, Illmensee et al 2006, and even inter-class iSCNT (Chen et al 2002, Liu et al 2004 nuclear transfer embryos were reported to have Pig-mouse cytoplasmic hybrid embryos developed to the blastocyst stage.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…It is difficult to draw firm conclusions from these papers. In general, embryos produced by NT underwent few cleavage divisions and only exceptionally reached the blastocyst stage [21][22][23][24]. It must be noted, however, that cytoplasts were sourced from oocytes that were either immature at the time of egg retrieval and were subsequently in vitro matured to metaphase II stage in culture, or from oocytes deemed unsuitable for IVF.…”
Section: Inconsistent Resultsmentioning
confidence: 99%